2013
DOI: 10.7314/apjcp.2013.14.12.7621
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HER2 Status in Breast Cancer: Comparison of Current Methods with MLPA and Real-time RT-PCR

Abstract: Human epidermal growth factor receptor (HER) status is an important prognostic factor in breast cancer. There is no globally accepted method for determining its status, and which method is most precise is still a matter of debate. We here analyzed HER2 mRNA expression by quantitative reverse transcription-PCR parallel, we performed a routine evaluation of HER2 protein by immunohistochemistry (IHC). To assess the (FISH) was used, substituting FISH when the results of IHC were ambiguous (2+) and for those IHC re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
0
12
0
2
Order By: Relevance
“…The HER2 gene is involved in intracellular signaling transduction pathways leading to cell growth and differentiation (Di Fiore et al, 1987;Kauraniemi et al, 2006;Unal et al, 2013). Studies have suggested that abnormal expression of HER2 gene by mutation or amplification may play an important role in tumor genesis (Auersperg et al, 2001;Garcia-Velasco et al, 2008;Cuadros and Villegras, 2009;Moatter et al, 2011;Duman et al, 2012;Pazhoomand et al, 2013;Unal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The HER2 gene is involved in intracellular signaling transduction pathways leading to cell growth and differentiation (Di Fiore et al, 1987;Kauraniemi et al, 2006;Unal et al, 2013). Studies have suggested that abnormal expression of HER2 gene by mutation or amplification may play an important role in tumor genesis (Auersperg et al, 2001;Garcia-Velasco et al, 2008;Cuadros and Villegras, 2009;Moatter et al, 2011;Duman et al, 2012;Pazhoomand et al, 2013;Unal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…HER2 has been reported to be overexpressed or amplified in a variety of human tumors (Nicholson et al, 2001;Rubin and Yarden, 2001;McAlpine et al, 2009;Ghaffari et al, 2011;Wang et al, 2011;Sardari et al, 2012;Duman et al, 2012;Panagiotou et al, 2012; RESEARCH ARTICLE Pazhoomand et al, 2013;Unal et al, 2013;Ziaian et al, 2014). The clinical significance of HER2 status in many tumor types is not yet clear except for breast, gastric, or gastroesophageal junction cancer patients (Nicholson et al, 2001;Gravalos and Jimeno, 2008;García-Velasco et al, 2008;Moatter et al, 2011;Wang et al, 2011;Duman et al, 2012;Pazhoomand et al, 2013;Tai et al, 2013;Unal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have previously studied the probability of HER‐2 2+ IHC breast cancers for HER‐2 amplification . In a study which was also in Iranian population 36% of HER‐2 2+ samples were HER‐2 amplified . Another study with a relatively large population of 1735 breast cancer HER‐2 amplification were seen in 14% of patients .…”
Section: Discussionmentioning
confidence: 90%
“…A recent report suggested that MLPA could rule out Her-2 amplification in 75% of ISH-evaluated Her-2-equivocal carcinomas [14]. Her-2 mRNA expression analysis by quantitative reverse transcription-PCR (qRT-PCR) may also be of help to determine the status of Her-2 [21]. Her-2 D-FISH equivocal cases determined by the ASCO/CAP 2013 guidelines always have an increase in CEP17 copy number and hence a <2.0 Her-2/CEP17 ratio.…”
Section: Discussionmentioning
confidence: 99%